Marseille, du Lacydon au faubourg Sainte-Catherine (Ve s. av. J.-C.-XVIIIe s.) Les fouilles de la place du Général-de-Gaulle - Bouiron, Marc (Documents d'archéologie française, 2001)
Recent archaeological operations have greatly increased om knowledge of the original Marseilles town centre and of neighbourhoods gradually incorporated into the city The excavations presented here carried out in 1992-1993 close to the Vieux Port and Canebière districts, have revealed abundant hitherto unknown information relating to shoreline occupation layers (dating from the 4th cent or,- HC to the setting up of salt-works m the early Middle Ages) as well as to developments on the town's periphery beyond the Plan fourmiguier fortifications In a previously rural area the suburb of Sainte-Catherine began to take shape, composed of several city blocks developed in conjunction with such construction protects as the Saint-Sépulcre hospital. The areawascompletely demolished in 1360 In the 18th century new construction began in the suburb which had become an integral part of the town m 1670 The new buildings were tom down at the beginning of the 19th century in order to make way for the Place du General- de-Gaulle, a major structural feature In the modern town of Marseilles